Developments in National Cancer Control Programmes in Europe – Results From the Analysis of a Pan-European Survey. (31st August 2021) - Jelenc, Marjetka; Weiderpass, Elisabete; Fitzpatrick, Patricia; Albreht, Tit
Introduction: National Cancer Control Programmes (NCCPs) provide a country's policy framework for the development of cancer control, focussing on the reduction of cancer morbidity and mortality and improving quality of life of cancer patients. Objective: Exploring and analysing to which extent some of the key elements of the European Guide for Quality National Cancer Control Programmes (Guide) are implemented in NCCPs in the EU. Methods: Survey carried out through 30 countries, EU members, Iceland, Montenegro, Norway and Turkey, focussing on stakeholders' participation, inclusion of all the envisaged chapters from the Guide as well as implementation and dissemination. Results: The results of the policy survey on European NCCPs carried out within Cancer Control Joint Action (CANCON JA) are presented. The response was 30 out of 35 countries. In total, 28 out of 30 countries, which completed the survey, had an NCCP or another cancer document. Cancer documents were mostly single documents, managed and supervised by the respective Ministries of Health and communicated to the public via websites and press. Nine documents were defined as programmes, eight as plans and six as strategies; in five countries, terminology was mixed. Regarding the content, recommended by the Guide from 2015, comprising ten chapter areas in three parts. Only 10 countries included in their NCCPs all elements suggested in the Guide. Conclusion: Based on our results, we can see that a more comprehensive approach in the process of NCCPs is needed. Policy should focus on the development of instruments for efficient cancer management, which would encompass the entire trajectory of the cancer care from diagnosis to survivorship and supportive care.